RETRACTED: RETRACTED: The Role of Intrinsic Motivation in Mediating the Influence of Situational Leadership Style on Performance - Anisa Anisa; Elwisam Elwisam; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to analyze The Role of Intrinsic Motivation in Mediating The Effect of Situational Leadership Style on Employee Performance at PT. Artha Alam Lestari. This study used primary data by distributing 100 questionnaires as respondents. Data were analyzed using Structural Equation Modeling analysis using AMOS 22 program. The results of the study showed that Situasional Leadership Style variable positive effected directly on Employee Performance, where Situasional Leadership Style that is applied will be able to improve Employee Performance. In addition, the Situational Leadership Style also positive effected indirectly on Employee Performance, which requires Intrinsic Motivation as an intervening variable to improve Employee Performance.